The Effect of Yacon Leaf Powder (Smallanthus Sonchifolius) on White Rats (Rattus norvegicus) Blood Glucose Levels with High Sugar Diet - Thatit Nurmawati; Sandi Alfa Wiga Arsa; Nawang Wulandari; Agus Saparudin (STIKes Patria Husada Blitar, 2021)
Maintaining a lifestyle can reduce the incidence of DM (diabetes mellitus). DM occurs due to insulin disorders so that blood glucose levels increase, which can lead to various complications. The management of blood glucose levels by activating the insulin function can be done by using natural ingredients such as the Yakon (Smallanthus sonchifolius) plant. Yakon leaves contain phenol which can reduce blood glucose. The design of this study was experimental with a pre-posttest approach with control-group design, using male and healthy white rats (Rattus norvegicus). Rats were divided into 3 groups, treatment dose 1, treatment dose 2 and control. The rats were given a high carbohydrate diet during 9 weeks to make the rats hyperglycemic. In the treatment group, dose 1 was 150 mg/kg BW, dose 2 was 300 mg kg BW, and was given for 3 days. The results showed that the rats in the treatment group dose 1 had decreased in the average blood sugar level of 114.10 mg / dl (p 0.002) and dose 2 was 105.27 mg / dl (p 0.005). This showed that there was an effect of treatments on blood sugar levels. The comparison results showed that there was a significant difference between the dose 1, the dose 2 group and the control (Sig. (2-tailed) = 0.001 (Î±) = 0.05). There was no significant difference in the treatment group dose 1 and treatment dose 2 (Sig. (2-tailed) = 0.693, (Î±) = 0.05). Yakon leaves can be used alternative to lower to control blood glucose levels in rats receiving a high-carbohydrate diet